Macroeconomics - Parkin, Michael 1939- (Pearson Education Limited, 2014)
What is economics? -- The economic problem -- Demand and supply -- Measuring GDP and economic growth -- Monitoring jobs and inflation -- Economic growth -- Finance, saving, and investment -- money, the price level, and inflation -- the exchange rate and the balance of payments -- Aggregate supply and aggregate demand -- Expenditure multipliers -- Inflation, jobs, and the business cycle -- Fiscal policy -- monetary policy -- International trade policy